ANALISIS FAKTOR PENERAPAN MANAJEMEN KESELAMATAN DAN KESEHATAN KERJA LINGKUNGAN : (Studi Kasus Proyek Rsud Suwiti, Petang Badung Bali) - I Kadek Mahesa Adi Saputra; I Nyoman Suta Widnyana (UNHI PRESS, 2026)
This study aims to analyze the factors influencing the implementation of Occupational Health, Safety, and Environmental Management (K3L) in the RSUD Suwiti Building Construction Project, Petang, Badung, Bali, considering the high risk of workplace accidents and the importance of protecting workers and the environment in construction projects. This research uses a quantitative approach with factor analysis to identify dominant variables affecting K3L implementation. Data were collected through questionnaires distributed to 42 respondents involved in the project, covering 25 indicators related to policy, planning, implementation, supervision, and working environment. Data analysis was conducted using SPSS through validity and reliability tests, as well as factor analysis using the Principal Component Analysis (PCA) method. The results show that all indicators are valid and reliable with a Cronbach’s Alpha value of 0.987. The data feasibility test indicates a Kaiser-Meyer-Olkin (KMO) value of 0.895 and a Bartlett’s Test significance of 0.000, confirming that the data are suitable for further analysis. The factor analysis results reveal a single dominant factor with an eigenvalue of 18.947, explaining 75.789% of the total variance, indicating that all variables are strongly related and form an integrated system. Therefore, the implementation of K3L in this project can be categorized as well-implemented, structured, and effective in supporting workplace safety and environmental protection.